2008
DOI: 10.1159/000121466
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms by Which <i>S</i>-Albuterol Induces Human Bronchial Smooth Muscle Cell Proliferation

Abstract: Background: Racemic albuterol is a 50:50 mixture of the R-isomer, levalbuterol, and the S-isomer, S-albuterol. S-Albuterol increases airway hyperresponsiveness to spasmogens, exacerbates asthmatic conditions and stimulates cell growth, whereas levalbuterol attenuates cell growth in culture. The mechanisms of S-albuterol-induced cell proliferation are not well understood. We studied the role of albuterol isomers and intracellular cell cycle regulators on proliferation of human bronchial smooth muscle cells. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 72 publications
1
13
0
1
Order By: Relevance
“…In a previous study, Tomlinson et al [24] showed that salbutamol, the racemic mixture of levalbuterol and (S)-albuterol, inhibited proliferation of human airway smooth muscle cells in culture. Later reports with HBSMC and racemic mixture of albuterol isomers [9,10] corroborated this report by Tomlinson et al [24] and further showed that treatment of the cells with levalbuterol alone resulted in inhibition of cell proliferation, while (S)-albuterol treatment stimulated cell growth. The present report is also in agreement with the previous reports cited above and further lends some insight into the biochemical pathways of (S)-albuterol-induced HBSMC proliferation in culture.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…In a previous study, Tomlinson et al [24] showed that salbutamol, the racemic mixture of levalbuterol and (S)-albuterol, inhibited proliferation of human airway smooth muscle cells in culture. Later reports with HBSMC and racemic mixture of albuterol isomers [9,10] corroborated this report by Tomlinson et al [24] and further showed that treatment of the cells with levalbuterol alone resulted in inhibition of cell proliferation, while (S)-albuterol treatment stimulated cell growth. The present report is also in agreement with the previous reports cited above and further lends some insight into the biochemical pathways of (S)-albuterol-induced HBSMC proliferation in culture.…”
Section: Discussionsupporting
confidence: 66%
“…However, recent pieces of evidence suggest that (S)-albuterol is not a true β 2 -adrenergic agonist [9,10,28,29,30]. Prolonged administration of racemic albuterol leads to increased airway responsiveness to spasmogens and may result in loss of asthma control [7,8,31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Future studies are warranted to: (1) further explore the mechanisms by which albuterol or formoterol exerts host defense functions. These include, but are not limited to, studies aimed at dissecting the involvement of β2-adrenergic receptor vs. other receptors such as platelet-activating factor (PAF) receptor and β1-adrenergic receptor[37]; and (2) determine if β2-agonists are able to reduce lung bacterial load in COPD patients, especially those with acute exacerbations.…”
Section: Discussionmentioning
confidence: 99%